2016
DOI: 10.3168/jds.2015-10730
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Evaluation of nitrogen excretion equations from cattle

Abstract: Nitrogen excretion in dairy manure is a precursor for N2O and NH3 formation in livestock housing, manure storage facilities, and after manure is applied to land. Nitrous oxide is a major contributor to greenhouse gas emissions, and reducing N output from dairy production facilities can reduce the amount of anthropogenic N2O entering the atmosphere. The objective of the study was to conduct a comprehensive evaluation of extant prediction models for N excretion in feces and urine using extensive literature data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 93 publications
(15 reference statements)
1
18
1
Order By: Relevance
“…The performance of FN prediction was intermediate (overall mean RMSPE = 21.3% and CCC = 0.59) compared with UN and TN predictions. In agreement with Johnson et al (2016) who indicated that equations developed by Reed et al (2015) for lactating cows resulted in greater prediction accuracy and less error compared with other exsiting models evaluated.…”
Section: Comparison Of Model Evaluation For the Five Forms Of N Excresupporting
confidence: 74%
See 2 more Smart Citations
“…The performance of FN prediction was intermediate (overall mean RMSPE = 21.3% and CCC = 0.59) compared with UN and TN predictions. In agreement with Johnson et al (2016) who indicated that equations developed by Reed et al (2015) for lactating cows resulted in greater prediction accuracy and less error compared with other exsiting models evaluated.…”
Section: Comparison Of Model Evaluation For the Five Forms Of N Excresupporting
confidence: 74%
“…An RMSPE value below 25% was deemed acceptable and an RMSPE below 10% of the mean was considered good. For error decomposition, mean or systemic bias larger than 5% of the total error was considered unacceptable (Johnson et al, 2016).…”
Section: Calculation Of Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestibility analytical methods were performed via methods utilized by Johnson et al (2016) . Three methods were used to evaluate the markers: the root mean square prediction error ( RMSPE ), the Nash–Sutcliffe efficiency ( NSE ), and the concordance correlation coefficient ( CCC ).…”
Section: Methodsmentioning
confidence: 99%
“…From a recent summary of published N balance studies on beef cattle offered high and low CP diets, Sánchez Chopa, Nadin, Agnelli, Trindade, and Gonda (2016) concluded that the effect of increased N intake on N-use efficiency was equivocal, with increases and decreases in efficiency observed across experiments. Compared to (lactating) dairy cows (Huhtanen, Nousiainen, Rinne, Kytölä, & Khalili, 2008;Kebreab, Strathe, Fadel, Moraes, & France, 2010;Warner et al, 2015;Whelan et al, 2017), there is much less understood about the relationships between beef cattle nutrition and N excretion (Johnson, Reed, & Kebreab, 2016;Waldrip, Todd, & Cole, 2013), and even less so in relation to beef cattle offered fresh grass (Sánchez Chopa et al, 2016).…”
mentioning
confidence: 99%